Relevance of cytochrome p450 levels in the actions of enflurane and isoflurane in mice: studies on the haem pathway - Buzaleh, Ana Maria (2001)
1. The effect of the fluorinated ether anaesthetics enflurane and isoflurane in mice on haem metabolism and regulation in different metabolic states, such as depression and induction of cytochrome P450 produced by allylisopropylacetamide (AIA) and imidazole, respectively, was investigated. 2. Mice previously treated with AIA (350 mg/kg, i.p.) or imidazole (400 mg/kg, i.p.) received a single dose (1 mL/kg, i.p.) of enflurane or isoflurane and were killed 20 min after anaesthetic administration. 3. Induction of δ-aminolevulinic acid synthetase (ALA-S) activity was found, as expected, in animals receiving AIA and also in animals treated with AIA plus anaesthesia, but no change in the activity of either porphobilinogenase (PBGase) or porphobilinogen deaminase (PBG-D) activities was detected in these two groups of animals. An additional increase in haem destruction was observed in the AIA plus isoflurane-treated group. When mice were injected with imidazol alone or in combination with the anaesthetics, ALA-S activity was increased 50-90% in all groups, but again no change in PBGase or PBG-D activity was observed. Haem oxygenase was diminished in mice receiving imidazole and anaesthesia. 4. In conclusion, neither enflurane nor isoflurane caused additional disturbances in haem metabolism to those produced by AIA or imidazole alone.